Mechanized direct- seeding and best management practices for rice in Cambodia : how and why are they complementary? - Aravindakshan, Sreejith; Krupnik, Timothy J.; Laing, Alison M.; Sokornthea Pin; Rica, Flor Joy; Saito, Kazuki (EiA, 2024)
Rice, a staple food source in Cambodia, constitutes 70% of the daily caloric intake and contributing nearly half of the country’s agricultural GDP (World Bank, 2019). As a top 10 global rice exporter (Tilleard et al., 2023), Cambodia seeks to enhance its role in regional and global food security amid challenges like climate change and rising input costs. National strategies, including the Sustainable Development Goals (2016–2030) and the National Agricultural Development Policy (2023–2030), highlight the need for sustainable production and trade. However, rice farmers face significant challenges, including low yields from poor crop establishment, high production costs, and labor shortages, reducing their global competitiveness. Addressing these challenges requires efficient, climate-resilient mechanization, such as mechanized direct-seeded rice (mDSR) (ADB, 2019). This policy note synthesizes evidence on mechanized direct-seeded rice (mDSR) technology in Cambodia based on a review and analysis of published papers, reports, grey literature and government documents. It contributes evidence to the Cambodian government’s rice productivity enhancement policy formulation by evaluating the benefits of mDSR compared to conventional rice planting methods. The information in this review is intended to lay the groundwork for subsequent efforts to scale the impact of mDSR scientifically and effectively within Cambodia’s rice production sector. Currently, rice sowing in Cambodia remains largely manual, with 99% of farmers relying on direct seeding methods (Flor et al. 2020). Among these, 80-90% still rely on hand-broadcast (bDSR) techniques, which, along with poor seed quality, lead to excessive seeding rates, inefficient fertilizer and pesticide use, and delayed crop maturity (Martin et al., 2021; Dunn et al., 2023). The lack of proper seed-soil contact in bDSR often results in poor germination and makes crops more vulnerable to pests and diseases, particularly in upland areas with compacted soils (Stuart et al., 2018; Nguyen-Van-Hung et al. 2024). In contrast, mechanized direct-seeded rice (mDSR) has shown considerable advantages. When integrated with best management practices—such as using high-quality seeds, implementing integrated weed management, applying biological control measures, and optimizing fertilizer use— mDSR can yield more than traditional bDSR methods (IRRI, 2022; Pame et al., 2023; Keo et al., 2023). Studies have reported yield increases of 26% to 50% in Kampong Thom and Takeo provinces, along with reduced labor and water use (ADB, 2019). Participatory trials conducted in 2022 across Prey Veng, Takeo, Battambang, and Kampong Thom demonstrated yield gains of up to 62% and labor savings of as much as 79%, emphasizing the efficiency of mDSR (IRRI, 2022; Pame et al., 2023). Net profits from mDSR also rose compared to traditional bDSR, with gains of 111% in Battambang, 296% in Prey Veng, and 120% in Kampong Thom, underscoring the economic advantages of this technology (IRRI, 2022; Pame et al., 2023). Advancing mDSR adoption in Cambodia requires strategic measures focused on research, technical support, and stakeholder collaboration. Continued research on mDSR technology and agronomic practices is essential, requiring collaboration among the Department of Agricultural Engineering under the General Directorate of Agriculture (GDA), the Department of Extension for Agriculture, Forestry and Fisheries (DEAFF), Cambodian Agricultural Research and Development Institute (CARDI), National Agricultural Research Systems, universities, Cambodian machinery manufacturers, and international research centers like CGIAR and ACIAR to drive innovation and ensure effective dissemination. Partnerships between the GDA and manufacturers can help tailor and enhance mDSR equipment, ensuring product quality, fostering innovation, and maintaining a consistent supply of spare parts. Additionally, improving access to high-quality seeds through a robust distribution network and stringent seed certification is essential for mDSR, as it can reduce weed seed contamination and enhance germination rates—critical factors for successful mDSR implementation. (Beecher et al., 2014; Saruth et al., 2014). Creating a supportive business environment for mechanization is equally crucial. Support from the Cambodian government in the form of low-interest financing and technical assistance could significantly advance agricultural mechanization business development, benefiting private companies, cooperatives, agri-startups and service providers (SPs). Financial incentives for laser land leveling (LLL) can address high land preparation costs and labor shortages, making mDSR adoption more feasible. Expanding models like the Cambodian Agricultural Value Chain Program (CAVAC) to co-finance mDSR equipment and support extension activities will foster a diverse network of SPs (Tan et al., 2019). Capacity building and knowledge-sharing should be led by agencies lie the DEAFF, CARDI, international research centers, NGOs, and private partners. With additional donor support, the Ministry of Agriculture, Forestry, and Fisheries (MAFF) will be well-positioned to create platforms for sharing mDSR information, engage social network brokers to connect farmers, service providers, and suppliers, and enhance trust and knowledge dissemination (Zhang et al., 2020). Comprehensive training on machinery operation, maintenance, and economic benefits, delivered through partnerships with GDA, DAEFF, CARDI, international research centers and universities, will further build farmer confidence in mDSR and promote its widespread adoption (Beecher et al., 2016; Hitzler, 2023).